Auditory guidance of eye movements toward threat-related images in the absence of visual awareness - Hu, Junchao; Badde, Stephanie; Vetter, Petra (Frontiers in Human Neuroscience, 2024)
The human brain is sensiIve to threat-related informaIon even when we are not aware of this informaIon. For example, fearful faces aLract gaze in the absence of visual awareness (VeLer et al., 2019). Moreover, informaIon in different sensory modaliIes interacts in the absence of awareness, for example, the detecIon of suppressed visual sImuli is facilitated by simultaneously presented congruent sounds or tacIle sImuli. Here, we combined these two lines of research and invesIgated whether threat-related sounds could facilitate visual processing of threat-related images suppressed from awareness such that they aLract eye gaze. We suppressed threat-related images of cars and neutral images of human hands from visual awareness using conInuous flash suppression and tracked observers' eye movements while presenIng congruent or incongruent sounds (finger snapping and car engine sounds). Indeed, threat-related car sounds guided the eyes towards suppressed car images, parIcipants looked longer at the hidden car images than at any other part of the display. In contrast, neither congruent nor incongruent sounds had a significant effect on eye responses to suppressed finger images. Overall, our results suggest that only in a dangerrelated context semanIcally congruent sounds modulate eye movements to images suppressed from awareness, highlighIng the prioriIsaIon of eye responses to threat-related sImuli in the absence of visual awareness.